The specifics of the construction of legal liability: issues of theoretical and practical modeling - Kuzmin, Igor (Journal of the Belarusian State University. Law, 2019)
The article is devoted to research a legal nature of the construction of legal liability. It is noted the low level of doctrinal elaboration of «legal construction» category. Based on analysis of issues, doctrinal and enforcement position the author comes to a conclusion about the importance of further study the construction of legal liability and denotes criteria of scientific research and the practical application the construction of liability in law.
Keywords: legal liability; legal construction; construction of legal liability; law enforcement practice; modeling